Mechanical Cocoa Podbreaker Utilization in Cocoa Handling to Improve Labor Efficiency - Sukrisno Widyoto; Sri Mulato; Siswoyo Soekarno (PERTETA, 2009)
One of initial step of primary cocoa processing, which determine the final quality and processing costwas pulping and pod breaker. Pod breaker is used to take out the cocoa bean and separate it from fruitcrust and placenta. Presently, cocoa pod breaking and bean separating from crust fruit are still conductedmanually and need many workers, as well. Indonesian Coffee and Cocoa Research Institute has designedand tested the cocoa pod breaker with double cylinder pod breaking mechanism and vibration table graderwith bean separating mechanism. Testing result showed that cocoa pod breaker had maximum workcapacity of 9000 cocoa pod per hour at motor rotation of 2,000-2,200 rpm. Highest percentage of crust chipincluded in bean was 1.1%, which was obtained at treatment input feeding opening of 80% and percentageof broken bean of 2.1%. While the lowest percentage of crust bean was 0.16% that is obtained at 20%input feeding opening with 1.7% of broken bean. Optimum work capacity of 4,950 cocoa pod per hour wasobtained at 50% input feeding opening with 0.22% crust chip included in bean, and 1.9% of broken beanpercentage.Keywords: cocoa, podbreaker, labor saving, production efficiencyDiterima: 3 Maret 2009; Disetujui: 16 Juli 2009